Assessing the genetic diversity of catface rockcod epinephelus andersoni in the subtropical Western Indian Ocean and modelling the effects of climate change on their distribution - Coppinger, Christine Rose (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
The catface rockcod Epinephelus andersoni is a range-restricted species that is endemic to the southeast coast of Africa from Quissico in Mozambique (subtropical) to Knysna in South Africa (warmtemperate). Its complex life-history, long-lived nature and high residency make E. andersoni potentially vulnerable to over-exploitation. Epinephelus andersoni is an important fishery species and has shown signs of depletion. Due to inadequate information necessary for management and conservation, further research is vital, particularly in the face of potentially significant climatic changes which could put further pressure on E. andersoni. The aim of the study was to provide information for the management of E. andersoni, with considerations for the possibly detrimental effects of future climate change. The objectives of this study were to describe the genetic structure and diversity of E. andersoni and to determine possible range shifts of E. andersoni with future changes in sea surface temperature. Genetic samples were collected throughout the distribution of E. andersoni. Standard DNA extraction and PCR using universal primers were conducted and nuclear (RPS7-1) and mitochondrial (cytochrome b) data were analysed to determine genetic diversity. A combination of nuclear and mitochondrial markers was used to ensure that the results were robust. RPS7-1 haplotype diversity was high (0.801) and an AMOVA on the RPS7-1 data showed significantly high among group variation (Î¦CT = 0.204, p < 0.05) between five groups: 1. Quissico to Inhaca; 2. Cape Vidal to Port Edward; 3 Port St Johns to Coffee Bay; 4. Mbashe; 5. Port Alfred. This geographic structuring could be attributed to low gene flow across barriers such as the Port Alfred upwelling cell, the Mozambique Channel eddies and smaller more localised upwelling cells such as the Port St Johns cell. The cytochrome b results contrastingly indicate low haplotype diversity (0.309) and no differentiation (Î¦CT = 0.265, p = 0.074) between groups and support the hypothesis of a historical population bottleneck. This may be due to an unusually slower mutation rate of the cytochrome b region than the RPS7-1 region, resulting in the RPS7-1 data showing a more recent picture of diversification. To complement the genetic results, niche modelling techniques were used to determine range shifts of E. andersoni with future temperature trends using species distribution and climatic data. The model illustrated a contraction of the E. andersoni distribution as well as future intensification of various upwelling cells along the south-east African coast including the Port Alfred upwelling cell. Due to the low gene flow across these barriers this intensification could decrease the resilience of E. andersoni, as its range becomes more limited with global change. The genetic data and modelling results combined provide useful information on which to base future fisheries management.
Keywords: Uncatalogued